Oxaliplatin combined with capecitabine therapy and comprehensive nursing in advanced colorectal cancer patients - Kuang, Dan; Xu, Hong; Shen, Xiaoming (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to discuss the influence of oxaliplatin combined with capecitabine therapy and comprehensive nursing in advanced colorectal cancer (CRC) patients.MethodsA total of 100 advanced CRC patients, selected from January 2019 to January 2021, were divided into a control group (CG) and a research group (RG). Patients in the CG received capecitabine tablets and underwent routine nursing, while those in the RG received capecitabine tablets along with intravenous infusion of oxaliplatin and underwent comprehensive nursing. The short-term effects, levels of tumor markers, immune function, quality of life, occurrence of adverse reactions, negative emotions, and long-term survival rate in both groups were compared.ResultsIn comparison to the CG, the RG exhibited a higher total effective rate (p < 0.05), lower cancer antigen 125 (CA125) and carbohydrate-associated antigen 199 (CA199) levels (p < 0.05), higher CD4+ and CD4+/CD8+ levels (p < 0.05), a higher Karnofsky performance status (KPS) score, a lower occurrence of adverse reactions (p < 0.05), lower Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores (p < 0.05), and a better long-term survival rate of patients after 2 years of follow-up (p < 0.05).ConclusionOxaliplatin combined with capecitabine therapy, with comprehensive nursing, can effectively reduce clinical symptoms, enhance the immune function, and improve the quality of life of advanced CRC patients.